L'agenda del lavoro (Firenze University Press, 2022)
This volume collects the best dissertations from the academic years 1999/00 and 2000/01 by students of the European Master in Work Sciences of the Department of Political Sciences "Cesare Alfieri" in Florence. The contributions focus on the theme of labour and its regulation in European countries, analysing aspects such as work flexibility, training, corporate industrial relations, corporate social responsibility, the promotion of participation of women and disabled people in the job market . These issues constitute privileged points of observation to highlight both the effects of promoting change in the process of European political integration and the role played by the presence of certain institutional architectures related to welfare, economic and work regulation systems that continue to differ from country to country. Looking at the coexistence between stability and change with a multidisciplinary and comparative approach like the one used in the works collected here is like using a kaleidoscope that helps to shed light on the multiple balances and on the different development paths that characterise the so-called "European social model".